Cu(ii)/SPDO complex catalyzed asymmetric Baeyer–Villiger oxidation of 2-arylcyclobutanones and its application for the total synthesis of eupomatilones 5 and 6. Issue 28 (6th July 2022) - Zhang, Chang-Sheng; Shao, Ya-Ping; Zhang, Fu-Min; Han, Xue; Zhang, Xiao-Ming; Zhang, Kun; Tu, Yong-Qiang
Abstract : A novel classical kinetic resolution of Baeyer–Villiger oxidation catalyzed by a Cu(ii )/SPDO complex with excellent enantioselectivity, regioselectivity and wide substrate scope is reported for the first time and explore the synthetic application. Abstract : A novel classical kinetic resolution of 2-aryl-substituted or 2, 3-disubstituted cyclobutanones of Baeyer–Villiger oxidation catalyzed by a Cu(ii )/SPDO complex is reported for the first time, producing normal lactones in excellent enantioselectivities (up to 96% ee) and regioselectivities (up to >20/1), along with unreacted ketones in excellent enantioselectivities (up to 99% ee). The current transformation features a wide substrate scope. Moreover, catalytic asymmetric total syntheses of natural eupomatilones 5 and 6 are achieved in nine steps from commercially available 3-methylcyclobutan-1-one.